Morality In Islam - Widya Masitah (Proceeding International Seminar of Islamic Studies, 2019)
Moral according to the teachings of Islam is when we do everything based on the Koran, while moral in society is when we do everything that is in accordance with the rules that apply in society. Moral is an important aspect that must be learned by everyone. At present there are many cases that illustrate moral degradation such as sexual harassment behavior, the use of illegal drugs and others. This of course needs improvement and the most important thing is improvement in the world of education where there must be moral cultivation in children based on the Koran and sunnah. The method used is the habituation method, storytelling method, exemplary method and others